Complete Chloroplast Genome Variants Reveal Discrete Long-Distance Dispersal Routes of Rhizophora in the Western Indian Ocean - Triest, Ludwig; Sierens, Tim; Van der Stocken, Tom (Frontiers in Conservation Science, 2021)
Historical processes of long-distance migration and ocean-wide expansion feature the global biogeographic pattern of Rhizophora species. Throughout the Indian Ocean, Rhizophora stylosa and Rhizophora mucronata seem to be a young phylogenetic group with an expansion of R. mucronata toward the Western Indian Ocean (WIO) driven by the South Equatorial Current (SEC). Nuclear microsatellites revealed genetic patterns and breaks; however, the estimation of propagule dispersal routes requires maternally inherited cytoplasmic markers. Here, we examine the phylogeography of 21 R. mucronata provenances across a >4,200 km coastal stretch in the WIO using R. stylosa as an outgroup. Full-length chloroplast genome (164,474 bp) and nuclear ribosomal RNA cistron (8,033 bp) sequences were assembled. The boundaries, junction point, sequence orientation, and stretch between LSC/IRb/SSC/IRa/LSC showed no differences with R. stylosa chloroplast genome. A total of 58 mutations in R. mucronata encompassing transitions/transversions, insertions-deletions, and mononucleotide repeats revealed three major haplogroups. Haplonetwork, Bayesian maximum likelihood (ML), and approximate Bayesian computation (ABC) analyses supported discrete historical migration events. An ancient haplogroup A in the Seychelles and eastern Madagascar was as different from other haplogroups as from R. stylosa. A star-like haplonetwork referred as the recent range expansion of haplogroup B from northern Madagascar toward the African mainland coastline, including a single variant spanning >1,800 km across the Mozambique Channel area (MCA). Populations in the south of Delagoa Bight contained haplogroup C and was originated from a unique bottleneck dispersal event. Divergence estimates of pre- and post-Last Glacial Maximum (LGM) illustrated the recent emergence of Rhizophora mangroves in the WIO compared to other oceans. Connectivity patterns could be aligned with the directionality of major ocean currents. Madagascar and the Seychelles each harbored haplogroups A and B, albeit among spatially separated populations, explained from a different migration era. Likewise, the Aldabra Atoll harbored spatially distinct haplotypes. Nuclear ribosomal cistron (8,033 bp) variants corresponded to haplogroups and confirmed admixtures in the Seychelles and Aldabra. These findings shed new light on the origins and dispersal routes of R. mucronata lineages that have shaped their contemporary populations in large regions of the WIO, which may be the important information for defining marine conservation units both at ocean scale and at the level of small islands.